Examination of pre-service science teachers' model based-content knowledge and knowledge of students’ understanding on chemical bonds - DURU, MEHMET KÜRŞAD (My University, 2023)
This study aims to examine pre-service science teachers\" (PSTs\") model-based (MB) content knowledge (CK) and knowledge of students\" understanding (KSU) of chemical bonds. The participants of the study consist of 229 senior pre service science teachers. The study is a case study from qualitative research designs. The data of the study were collected by using the \"Chemical Bonds Model Knowledge Test (CBMKT)\". The obtained data were analyzed using the \"Model BasedContent Knowledge Rubric (MB-CK Rubric)\" and \"Model Based-Knowledge of Students\" Understanding Rubric (MB-KSU Rubric)\". The findings showed that PSTs mostly have an understanding of wrong modeling and not being able to make any modeling in terms of MB-CK on chemical bonds. In addition, it has been determined that the majority of pre-service teachers have an invalid and weak level in terms of MB-KSU. These findings indicate that PSTs\" professional knowledge of chemical bonds in their undergraduate education should be supported by modelbased teaching.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Fen Bilgisi Öğretmenliği; Social Sciences and Humanities; Education; Teacher Training in Natural Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Chemical bonds; Modeling knowledge; Knowledge of students’ understanding; Preservice science teachers